A novel electrochemical immunosensor based on PdAgPt/MoS2 for the ultrasensitive detection of CA 242 - Cao, Linlin; Lu, Sumei; Guo, Chengjie; Chen, Wenqiang; Gao, Yinan; Ye, Diwen; Guo, Zejun; Ma, Wanshan (Frontiers in Bioengineering and Biotechnology, 2022)
Dynamic monitoring of tumor markers is an important way to diagnose tumor, evaluate the therapeutic effect of tumor and analyze the prognosis of tumor. As a tumor marker of digestive tract, CA242 is often used to Assess the therapeutic effect of colorectal cancer and pancreatic cancer. In this study, immunosensor technology was used to detect CA242. PdAgPt nanocomposites, which have great advantages in biocompatibility, electrical conductivity and catalytic properties, were prepared by hydrothermal synthesis method. The prepared PdAgPt nanocomposites were loaded onto the surface of molybdenum disulfide (MoS2) with large surface area, and the new nanocomposites were synthesized. Using PdAgPt/MoS2 as signal amplification platform, the label-free CA242 electrochemical immunosensor has a wide detection range that extends from 1*10-4 U/ ml to 1 *102 U/mL and a low detection limit (LOD, 3.43*10-5 U/mL) after optimization of experimental conditions. In addition, the CA242 immunosensor designed in this study also performed well in the evaluation of repeatability, selectivity and stability, and was successfully used for human serum sample detection. Therefore, the label-free electrochemical immunosensor constructed in this study has a broad application prospect in the detection of clinical biomarkers.